2011
DOI: 10.1186/cc10338
|View full text |Cite
|
Sign up to set email alerts
|

Lung sonography and recruitment in patients with early acute respiratory distress syndrome: A pilot study

Abstract: IntroductionBedside lung sonography is a useful imaging tool to assess lung aeration in critically ill patients. The purpose of this study was to evaluate the role of lung sonography in estimating the nonaerated area changes in the dependent lung regions during a positive end-expiratory pressure (PEEP) trial of patients with early acute respiratory distress syndrome (ARDS).MethodsTen patients (mean ± standard deviation (SD): age 64 ± 7 years, Acute Physiology and Chronic Health Evaluation II (APACHE II) score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 43 publications
2
37
0
1
Order By: Relevance
“…Indeed, lung ultrasonography has been demonstrated to be superior to bedside chest radiography not only in the detection, but also in the follow-up, of pneumothorax after pleural drainage [36,41]. Ultrasound was also able to show recruitment of lung parenchyma as PEEP was increased from 5 to 15 cmH 2 O with correlation to improvement of gas exchange [42].…”
Section: Lung Ultrasonographymentioning
confidence: 81%
“…Indeed, lung ultrasonography has been demonstrated to be superior to bedside chest radiography not only in the detection, but also in the follow-up, of pneumothorax after pleural drainage [36,41]. Ultrasound was also able to show recruitment of lung parenchyma as PEEP was increased from 5 to 15 cmH 2 O with correlation to improvement of gas exchange [42].…”
Section: Lung Ultrasonographymentioning
confidence: 81%
“…A subsequent study showed that lung reaeration can be estimated accurately with bedside lung US. 7 Recently, Rode et al 8 proposed that lung US could guide lung recruitment by using PEEP, with improvement in lung consolidation as a sign of improved alveolar ventilation. Presently, there is no systematic USguided lung recruitment protocol available for clinical use.…”
mentioning
confidence: 99%
“…The LAS has been shown in several studies to correlate with changes in lung aeration after pneumonia treatment [21], PEEP titration [23], fluid resuscitation [24 • ], and spontaneous breathing trials [25]. Furthermore, an abbreviated technique of quantifying non-aerated region by planimetry at the dependent region of the right lung along the posterior axillary line has also correlated well with changes in PEEP in a pilot study [26].…”
Section: Evaluation Of Lung Aerationmentioning
confidence: 89%